A Potential Mechanism of Sodium Channel Mediating the General Anesthesia Induced by Propofol - Xiao, Jinglei; Chen, Zhengguo; Yu, Buwei (Frontiers in Cellular Neuroscience, 2020)
General anesthesia has been a significant scientific advance, and has revolutionized healthcare over the past 200 years. However, many phenomena induced by general anesthetics including paradoxical excitation are still poorly understood. Voltage-gated sodium channels (NaV ) were believed to be one of the proteins targeted during general anesthesia. Based on electrophysiological measurements before and after propofol treatments of different concentrations, we mathematically modified the Hodgkin-Huxley sodium channel formulations and constructed a thalamocortical model to investigate the potential roles of NaV . The ion channels of individual neurons were modelled using Hodgkin-Huxley type equations. The enhancement of the GABAa current induced by propofol was simulated by increasing the maximal conductance and the time-constant of decay. EEG was evaluated as the post-synaptic potential from pyramidal cells. We found that a left shift in activation of NaV was induced primarily by a low concentration of propofol (0.3 uM-10 uM), while a left shift in inactivation of NaV was induced with increasing concentration (0.3 uM-30 uM). Mathematical simulation indicated that a left shift of NaV activation produced a Hopf bifurcation, leading to cell oscillations. Left shift of NaV activation around a value of 5.5 mV in thalamocortical models suppressed normal bursting of TC cell by triggering its chaotic oscillations. It led to irregular spiking of PY cell and an increased frequency in EEG readings. This observation suggests a mechanism leading to paradoxical excitation during general anesthesia. While a left shift in inactivation led to light hyperpolarization in individual cells, it inhibited the activity of the thalamocortical model after a certain depth of anesthesia. This finding implies that high doses of propofol inhibit the network partly by accelerating NaV towards inactivation. Additionally, this result explains why the application of sodium channel blockers decreases the requirement for general anesthetics. Our study provides an insight into the roles that NaV plays in the mechanism of general anesthesia. Since the activation and inactivation of NaV are structurally independent, it should be possible to avoid side effects by state-dependent binding to the NaV to achieve precision medicine in the future.